USP42 protects ZNRF3/RNF43 from R‐spondin‐dependent clearance and inhibits Wnt signalling - Giebel, Nicole (EMBO Rep, 2021)
The tumour suppressors RNF43 and ZNRF3 play a central role in development and tissue homeostasis by promoting the turnover of the Wnt receptors LRP6 and Frizzled (FZD). The stem cell growth factor R‐spondin induces auto‐ubiquitination and membrane clearance of ZNRF3/RNF43 to promote Wnt signalling. However, the deubiquitinase stabilising ZNRF3/RNF43 at the plasma membrane remains unknown. Here, we show that the USP42 antagonises R‐spondin by protecting ZNRF3/RNF43 from ubiquitin‐dependent clearance. USP42 binds to the Dishevelled interacting region (DIR) of ZNRF3 and stalls the R‐spondin‐LGR4‐ZNRF3 ternary complex by deubiquitinating ZNRF3. Accordingly, USP42 increases the turnover of LRP6 and Frizzled (FZD) receptors and inhibits Wnt signalling. Furthermore, we show that USP42 functions as a roadblock for paracrine Wnt signalling in colon cancer cells and mouse small intestinal organoids. We provide new mechanistic insights into the regulation R‐spondin and conclude that USP42 is crucial for ZNRF3/RNF43 stabilisation at the cell surface.